2020
DOI: 10.3390/w12030759
|View full text |Cite
|
Sign up to set email alerts
|

Water–Air Interface Greenhouse Gas Emissions (CO2, CH4, and N2O) Emissions Were Amplified by Continuous Dams in an Urban River in Qinghai–Tibet Plateau, China

Abstract: Continuous dams may lead to great variation in greenhouse gas (GHG) emissions from rivers, which contribute more uncertainty to regional carbon balance. This study is among the first to determine water–air interface GHGs (CO2, CH4, and N2O) in a river with continuous dams in plateau city. Combined static-chamber gas and meteorological chromatography were utilized to monitor the GHGs emission flux at the water–air interface within four continuous dams in the Huoshaogou River in the Qinghai–Tibet Plateau, China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Such pattern of N 2 O concentrations was consistent with previous reports in other single or cascaded river-reservoir systems (Liu et al, 2009b;Liu et al, 2011a;Liu et al, 2017;Cheng et al, 2019). For example, Yang et al (2020) found that the N 2 O emissions in the impoundment-affected Huoshaogou River were much higher than the upper rivers as influenced by enrichment of N and OC in sediment after river damming. Liu et al (2017) also found that the N 2 O emission fluxes in released water sections were five times higher than those in reservoir sections in Dongfeng Reservoirs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such pattern of N 2 O concentrations was consistent with previous reports in other single or cascaded river-reservoir systems (Liu et al, 2009b;Liu et al, 2011a;Liu et al, 2017;Cheng et al, 2019). For example, Yang et al (2020) found that the N 2 O emissions in the impoundment-affected Huoshaogou River were much higher than the upper rivers as influenced by enrichment of N and OC in sediment after river damming. Liu et al (2017) also found that the N 2 O emission fluxes in released water sections were five times higher than those in reservoir sections in Dongfeng Reservoirs.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, it is well known that hydraulic residence time could govern N processing time and gaseous N emissions in rivers (Hohener and Gachter, 1993;Harrison et al, 2008; Alexander et al, 2009) and that the long hydrological residence time allowed bacteria to settle down and to drive nitrogen mineralization and decomposition (Wang et al, 2018a;Chen et al, 2020;Deng et al, 2020). Thus, the hydraulic residence time and related hydrologic load have been considered as the important factors driving the variations of N 2 O concentrations in cascade reservoirs (Liang et al, 2019;Shi et al, 2020;Yang et al, 2020). In this study, the N 2 O concentrations and fluxes were found to be positively correlated with hydraulic residence time and negative with hydraulic load significantly (Figure 7), implying the regulating and controlling of hydrological conditions on the spatial variations of N 2 O emissions in the Wubu River cascaded reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of space, the peak of biomass appeared in the first barrage. It may be associated with the fact that organic matter tends to deposited behind the first dam (Yang et al, 2020). Zooplankton had the largest growth among the three organisms, while it also presented the largest temporal and spatial fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…In China, small rubber dams are often constructed continuously on a river for tens of kilometers, and thus their cumulative effect can be significant, especially for plateau areas where river ecosystems are fragile (Dong, Liu, Liu, Wang, & Wang, 2014; Yang et al, 2020). The current study focuses on the cascaded rubber dams in an urban river of the Qinghai‐Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%